Inhibition of the procarboxypeptidase U (proCPU, TAFI, proCPB2) system due to hemolysis. (2nd May 2019) - Mertens, Joachim C.; Claesen, Karen; Leenaerts, Dorien; Sim, Yani; Lambeir, Anne‐Marie; Hendriks, Dirk
Abstract : Essentials Hemolytic influence on the (pro)carboxypeptidase U ((pro)CPU) system is not known. In the current manuscript, this was assessed by spiking pooled normal plasma with hemolysate. CPU activity, proCPU levels, and clot lysis times showed a dose‐dependent hemolytic bias. The observed bias in the several CPU related parameters is due to inhibition of CPU activity. Introduction: Spurious hemolysis of samples is the leading cause of interference in coagulation testing and was described to interfere in fibrinolysis assays. The influence of hemolysis on the procarboxypeptidase U (proCPU) system is not known. Methods: By means of spiking of hemolysate in pooled normal plasma, the effect of hemolysis on CPU, proCPU, and functional clot lysis assays was assessed. The influence of hemolysis on CPU generation during in vitro clot lysis was also evaluated. Cutoffs corresponding to maximal acceptable bias were determined. Results and discussion: When active CPU was added to pooled plasma, a severe decrease in activity – up to 97.2% inhibition – was seen with increasing plasma concentrations of oxyhemoglobin (oxyHb) and the 10% cutoff value was found to be 0.3 g/L oxyHb. Using an activity‐based assay, proCPU levels appeared to decrease gradually with increased hemolysis (maximal reduction of 19.5%) with a 10% cutoff value of 4.2 g/L oxyHb. The relative clot lysis time (CLT) showed a maximal negative bias of 68.5%. The reduction in CLT paralleled a significant reduction of the first CPU activity peak during clot lysis. The cutoff value for the CLT was 0.4 g/L oxyHb. In presence of thrombomodulin (TM), CLT+TM was not affected up to 8.0 g/L oxyHb. Conclusion: These data indicate a clear inhibition of the CPU system because of hemolysis resulting in an increase of lysis in functional fibrinolysis assays. We were able to quantify the inhibitory effect and to propose cutoff values for every parameter.